General Principles and Challenges of Public Administration Organization in Slovenia - Nikolić, Bruno; Brezovar , Nejc (General Principles and Challenges of Public Administration Organization in Central Europe, 2024)
Slovenia is a democratic parliamentary republic. Citizens exercise power directly (e.g. referendum) and through elections, in line with the principle of the separation of powers. Power is divided into the legislative (Parliament, which consists of the National Assembly and the National Council), executive (Government and President of the Republic of Slovenia), and judicial branches. Although the President of the Republic is considered the nominal head of executive power, the government is the de facto holder of executive power. The principle of separation of powers is not implemented in a ‘pure’ form due to several elements that disrupt the relations between the different branches of government. There is an imbalance in this relationship favouring the legislature, which is reflected in the significant power of the National Assembly in appointing officials and, conversely, the limited power of the President of the Republic. The state administrative bodies in Slovenia include government offices, various government departments, ministries, and different bodies within ministries and administrative units. The government comprises a President and ministers. Government and state administration are closely related, with the government also serving as the largest body within the state administration in the Republic of Slovenia. The government represents the top of the political executive power structure, while the state administration is the professional part of executive power. State administration, governed by fundamental principles, constitutes a collection of state bodies that develop the professional basis for the government’s political decision-making and directly execute decisions issued by both the government and parliament. Administrative units carry out the tasks of state administration, which must be organized and implemented uniformly across any of the state’s 58 administrative units. In addition to administrative decentralisation through these units, the Constitution guarantees territorial decentralisation through local self-government. Slovenian local self-government has only one level – the municipal level – comprising 212 municipalities. In recent years, Slovenian public administration has faced the following main challenges, which will determine its further development: reform of the salary system, public authority dilemmas, regional establishment, number of municipalities, and financing methods.KEYWORDS Slovenia, public administration, constitutional order, organizational principles, structure of the public administrationBibliographyBrezovnik, B. (2008) ‘Decentralizacija v teoriji in praksi’, Lex Localis, 6(1) pp. 87–103 [Online]. Available at: https://doi.org/10.4335/33 (Accessed: 15 February 2024).European Commission (2023) Slovenia [Online]. Available at: https://eurydice.eacea.ec.europa.eu/national-education-systems/slovenia/population-demographic-situation-languages-and-religions (Accessed 24 May 2023).Goldmann, M. (2018) ‘Public and Private Authority in a Global Setting: The Example of Sovereign Debt Restructuring’, Indiana Journal of Global Legal Studies, 25(1), pp. 331–363 [Online]. Available: https://doi.org/10.2979/indjglolegstu.25.1.0331 (Accessed: 15 February 2024).Government Communication Office (2021) A short history of Slovenia [Online]. Available at: https://www.gov.si/en/news/2021-04-14-a-short-history-of-slovenia/ (Accessed: 24 May 2023).Gov.SI Portal (2023) Political system [Online]. Available at: https://www.gov.si/en/topics/political-system/ (Accessed: 27 May 2023).Grad, F., Kaučič, I., Zagorc, S. (2018) Ustavno pravo. Druga, spremenjena in dopolnjena izdaja. Ljubljana: Pravna fakulteta Univerza v Ljubljani.Grechenkova, O.Y. (2022)’President of the Russian Federation in the national security s y s t e m ’, Dela Press Conference Series: Humanities and Social Sciences, 001(018) pp. 1–9 [Online]. Available at: https://doi.org/10.56199/dpcshss.zof b2749 (Accessed: 15 Februar y 2024).Haček, M. (2020) ‘Financial Autonomy of the Slovenian Local Government’, Journal of Comparative Politics, 13(2), pp. 86–98.Johnston, J. (2015) ‘Public Administration: Organizational Aspects’ in Wright, J.D. (ed.) International Encyclopedia of the Social & Behavioral Sciences. 2nd edn. Oxford: Elsevier, pp. 521–525; https://doi.org/10.1016/B978-0-08-097086-8.73057-1.Kjaer, P.F. (2018) ‘From the Private to the Public to the Private? Historicizing the Evolution of Public and Private Authority’, Indiana Journal of Global Legal Studies, 25(1), pp. 13–36 [Online]. Available at: https://doi.org/10.2979/indjglolegstu.25.1.0013 (Accessed: 15 February 2024).Kovač, P. (2006) Pravni in sociološki vidiki javnih pooblastil. Ljubljana: Fakulteta za upravo, Univerza v Ljubljani.Lavrencic, K., Allcock, J.B., Barker, T.M. (2023) Slovenia [Online]. Available at: https://www.britannica.com/place/Slovenia (Accessed: 24 May 2023).Stanojević, M., Poje, A. (2019) ‘Slovenia: Organised decentralisation in the private sector and centralisation in the public sector’ in Müller, T., Vandaele, K., Waddington, J. (eds.) Collective bargaining in Europe: towards an endgame. Volume I, II, III and IV. Brussels: The European Trade Union Institute [Online]. Available at: https://www.etui.org/publications/books/collective-bargaining-in-europe-towards-an-endgame-volume-i-ii-iii-and-iv (Accessed: 23 April 2024).OECD (2011) OECD Territorial Reviews: Slovenia 2011. OECD Territorial Reviews. Paris: OECD Publishing; https://doi.org/10.1787/9789264120587-en. O’Neill, A. (2023) Slovenia: Share of economic sectors in the gross domestic product (GDP) from 2011 to 2021 [Online]. Available at: https://www.statista.com/statistics/329073/share-of-economic-sectors-in-the-gdp-in-slovenia/ (Accessed: 24 May 2023). Pečarič, M. (2018) Osnove splošnega upravnega prava. Ljubljana: Fakulteta za upravo, Univerza v Ljubljani. Pirnat, R. (2019) Opredelitev člena in razmerje do drugih ustavnih institutov — E-KURS [Online]. Available at: http://e-kurs.si/komentar/opredelitev-clena-in-razmerje-do-drugih-ustavnih-institutov-2019-02-47/ (Accessed: 1 June 2023). Rakar, I. (2021) ‘Public Administration Organization’ in Stare, J., Pečarič, M. (eds.) The Science of Public Administration. Ljubljana: The Faculty of Public Administration, University of Ljubljana, pp. 309–330. Rakar, I., Klun, M. (2019) ‘Slovenia’ in Geissler, R., Hammerschmid, G., Raffer, C. (eds.) Local public finance in Europe: country reports. Gütersloh: Bertelsmann Stiftung, pp. 181–192. Slovenian Business portal (2023) Slovenia country profile [Online]. Available at: https://poslovniportal.si/en/doing-business-slovenia/i-slovenia-country-profile (Accessed: 24 May 2023). Slovenia Business (2023) Macroeconomic Overview [Online]. Available at: https://www.sloveniabusiness.eu/business-environment/slovenias-robust-economy (Accessed: 24 May 2023). SURS (2023a) Earnings [Online]. Available at: https://www.stat.si/statweb/en/Field/Index/15/74 (Accessed: 24 May 2023). SURS (2023b) Government Deficit and Debt, Government Accounts [Online]. Available at: https://www.stat.si/statweb/en/Field/Index/1/86 (Accessed: 24 May 2023). Šturm, L. (2002a) ‘Ustavnosodna presoja – E-KURS’, Komentar Ustave Republike Slovenije, 2022. [Online]. Available at: https://e-kurs.si/komentar/ustavnosodna-presoja-68/ (Accessed: 1 June 2023). Šturm, L. (2002b) ‘Opredelitev in razmerje do drugih ustavnih določb – E-KURS’,Komentar Ustave Republike Slovenije, 2022. [Online]. Available at: https://e-kurs.si/komentar/opredelitev-in-razmerje-do-drugih-ustavnih-dolocb-41/ (Accessed: 1 June 2023). Šturm, L. (2002c) ‘Dolžnost obrazložitve konkretnega upravnega akta – Vsebina in obseg obrazložitve – E-KURS’, Komentar Ustave Republike Slovenije, 2022. [Online]. Available at: https://e-kurs.si/komentar/dolznost-obrazlozitve-konkretnega-upravnega-akta-vsebina-in-obseg-obrazlozitve/ (Accessed: 1 June 2023). Šturm, L. (2010) Komentar Ustave Republike Slovenije. Kranj: Fakulteta za državne in evropske študije. Šturm, L. (2011) Komentar Ustave Republike Slovenije. Kranj: Fakulteta za državne in evropske študije. Tičar, B., Rakar, I. (2011) Pravo javnega sektorja. Maribor: Inštitut za lokalno samoupravo in javna naročila.Virant, G. (2002) ‘Organisation and Work of the State Administration (par. 1 of Article 120) – E-KURS’, Komentar Ustave Republike Slovenije, 2022. [Online]. Available at: https://e-kurs.si/komentar/organizacija-in-pristojnosti-uprave-imenovanja-funkcionarjev-1-odst-120-clena/ (Accessed: 1 June 2023).Worldometer (2023) Slovenian population [Online]. Available at: https://www.worldometers.info/world-population/slovenia-population/ (Accessed: 24 May 2023).